Ghrelin and melatonin as biomarkers in patients with giardiasis - Saleem Khteer Al-Hadraawy; Mohammed Emad Al-ghurabi; Malak Maged Al-musawi; Mohammad Alzeyadi (Biotechnology & Biotechnological Equipment, 2016)
Giardia is the most frequently reported intestinal parasite worldwide. The aim of this study was to investigate the ghrelin, melatonin, glucose and cholesterol concentration in male patients infected with Giardia lamblia. We enrolled 66 patients with Giardiasis and the control groups consisted of healthy subjects (n = 30). The results demonstrated that there was a significant decrease (P < 0.05) in ghrelin levels, while the melatonin, glucose and cholesterol levels were significantly increased (P < 0.05) in giardiasis patients as compared to the healthy group. The obtained results suggest that ghrelin and melatonin could serve as biomarkers in patients infected with G. lamblia.